Optimization of a peptide-based protocol employing IL-7 for in vitro restimulation of human cytotoxic T lymphocyte precursors. - Lalvani, A; Dong, T; Ogg, G; Patham, A; Newell, H; Hill, A; Mcmichael, A; Rowland-Jones, S (1997)
A variety of different methods for the in vitro restimulation of human cytotoxic T lymphocyte (CTL) precursors (CTLp) are in use. Our aim was to enhance the detection of circulating human CTLp in peripheral blood. We have developed a standardized and highly efficient method for restimulating CTLp. Synthetic peptides were used to restimulate cognate CTLp from peripheral blood mononuclear cells (PBMC), and effector CTL capable of lysing peptide-pulsed and virus infected targets were generated. The effects of several parameters on CTL specific for influenza A, EBV and HIV-1 were evaluated, and the optimum peptide concentration for CTL generation was established. Supplementation of initial cultures with IL-7 greatly enhanced peptide-specific lytic activity for all peptides tested and the dose-response relationship for IL-7 was delineated. A novel technique using peptide-MHC class I molecule tetramers to stain T cells bearing cognate T cell receptors permitted enumeration of antigen-specific CD8 + CTL during in vitro restimulation; IL-7 supplementation selectively expanded the population of peptide-specific CD8 + CTL. Importantly, this protocol, whilst enhancing the restimulation and lytic activity of secondary CTL, does not induce primary CTL in vitro. The improved efficiency with which CTL are generated in this system substantially enhances the sensitivity of CTL culture and the 51Cr release assay to detect low levels of CTL activity.